Hardware Simulation of Active Lane Keeping Assist Based on Fuzzy Logic - Noor Cholis Basjaruddin; Kuspriyanto Kuspriyanto; Didin Saefudin; Alditama Rachman (Institute of Advanced Engineering and Science, 2017)
Accidents due to cross the lane (lane departure crash) of achieving 19% of all accidents. These accidents mostly caused because the driver is not concentrating or dozing. A device that can help the driver so that the vehicle does not exit lanes known as Active Lane Keeping Assist (ALKA). ALKA is a subsystem of Advanced Driver Assistance System (ADAS) and is now used in several brands of cars namely Audi, BMW, and Ford. ALKA useful to help the driver, especially on roads with monotonous situations such as toll roads. This paper presents the development of fuzzy logic-based algorithm for ALKA. A battery toy car is used as a hardware simulation to test the algorithm in real time situation. The test results at three different speeds are slow, medium, and high indicate that the algorithm can work according to design.